Capital Structure, Internal Governance Mechanisms And Firm Performance - Bin Noor Helmy, Muhammad Harith Zulqarnain; Fei, Goh Chin; Kowang, Tan Owee; Hee, Ong Choon; Teck, Tan Seng; Yew, Lim Kim; Hoo, Wong Chee (International Journal of Psychosocial Rehabilitation, 2020)
This study examines the impact of capital structure and internal governance mechanisms on Malaysian manufacturing firms’ performance. A total of 183 companies were selected from the list of listed companies in Bursa Malaysia within the year 2007 to 2010. We collect the corporate governance data from the annual financial data from Thompson Reuter’s DataStream. The study shows the positive impact of capital structure on firm performance of manufacturing firms in Malaysia. However, this study found CEO duality and independent director do not affect firm performance. The implication of this study is that the manufacturing firms in Malaysia should achieve optimal capital structure in improving firm performance.